Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/arcm.12336
|View full text |Cite
|
Sign up to set email alerts
|

Portuguese Blue‐on‐Blue 16th–17th Century Pottery

Abstract: Blue‐on‐blue (‘berettino’) sherds have appeared in numerous production and consumption archaeological excavations in Lisbon and other archaeological sites in Portugal (dated from the mid‐16th century to the beginning of the 17th century). The abundance of this interesting faience led us to compare it with similar pottery from other well‐known production centres in Italy, namely Liguria (Savona and Albisola), Spain (the Triana kilns) and the Low Countries. Differences in the diffraction patterns of the sherds' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 32 publications
3
14
0
Order By: Relevance
“…The Raman technique failed to identify the colouring ions that don't form complexes or crystallites. Diffuse reflectance spectroscopy [89,91], portable XRF [91,92] or Synchrotron µXRF/diffraction [93] should be also very useful.…”
Section: Discussionmentioning
confidence: 99%
“…The Raman technique failed to identify the colouring ions that don't form complexes or crystallites. Diffuse reflectance spectroscopy [89,91], portable XRF [91,92] or Synchrotron µXRF/diffraction [93] should be also very useful.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio R = (SiO 2 + Al 2 O 3 + K 2 O)/CaO is used here to quantify the relative amounts of the structural and most abundant components of the ceramic pastes, the components related to detrital/siliciclastic minerals (SiO 2 + Al 2 O 3 + K 2 O) and the components related to chemical soluble fractions (CaO). This approach was used in previous recent publications from our group . All the 23 sherds were also analysed, and data are presented in Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Further reports about the use of this spectroscopic tool can be found in references. [18,[20][21][22][23][24]…”
Section: Micro-raman Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Ceramic bodies (pastes) were analyzed either from a recently scraped surface of the sherds or from ground sherd fragments (10-20 mg). Further details about the use of this spectroscopic tool for the study of ancient Portuguese ceramics can be found in references [15][16][17][18][19].…”
Section: Raman Microspectrometry Setupmentioning
confidence: 99%